Xanthogranulomatosis of the spleen: a case report - Goshi Fujimoto; Ken Hayashi; Shigetoshi Yamada; Hiroshi Kusanagi; Koichi Honma (Surgical Case Reports)
Abstract Background Xanthogranulomatous inflammation is recognized as a subtype of cholecystitis; however, it can also occur in other organs. Xanthogranulomatosis of the kidney, bone, ovary, endometrium, vagina, prostate, lymph nodes and pancreas was reported. Herein, we report a case of laparoscopic splenectomy in a patient with xanthogranulomatosis of the spleen that was difficult to diagnose preoperatively. Case presentation A 63-year-old man with a past medical history of hyperlipidemia had gradually growing multiple splenic masses, which were revealed on abdominal ultrasonography. Preoperative imaging suggested hamartoma, extramedullary hematopoiesis, or an inflammatory pseudotumor. Although metastatic splenic tumors and malignant lymphoma are atypical, they were considered in the differential diagnosis. Thus, laparoscopic splenectomy was performed. Pathological results confirmed a diagnosis of splenic xanthogranulomatosis. An increase in the postoperative triglyceride levels indicated that hyperlipidemia was the cause of xanthogranulomatosis of the spleen. Conclusions Xanthogranulomatosis should be considered in the differential diagnosis of multiple splenic mass lesions in patients with splenomegaly. Additionally, fine-needle aspiration biopsy should be considered for the preoperative diagnosis.